Cerebellar vermis area in schizophrenic patients: a post-mortem study - Supprian, Tillmann; Ulmar, Gerd; Bauer, Manfred; Schüler, Michael M.; Püschel, Klaus; Retz-Junginger, Petra; Schmitt, Horst Peter; Heinsen, Helmut (Schizophrenia research, 2000)
Neuroimaging studies of cerebellar atrophy in schizophrenia have yielded contradictory results. In computer-tomography (CT) studies, cerebellar atrophy was found in up to 40% of schizophrenic patients. However, several recent magnetic resonance imaging (MRI) studies could not replicate these early findings; in addition, contradictory observations of enlargement of vermal structures were reported. In contrast to the number of CT and MRI studies, there are only a few neuropathological reports on this subject. In a post-mortem study we analyzed the midsagittal vermal area of formaldehyde-fixed cerebella of 12 deceased schizophrenic patients and 12 age- and gender-matched control subjects by using morphometrical methods. Statistical analysis using ANOVA revealed no significant group effects, but there were interactions with gender and cerebellar brain weight. In view of the present results, the common concept of cerebellar atrophy in schizophrenic patients appears premature. Gender effects and secondary processes (e.g., relevant alcohol or drug abuse) cannot be excluded as possible factors causing decrease of vermal areas in schizophrenic patients.